Benarkah Musik Klasik Bertempo Lambat Mengganggu Pemahaman Bacaan Mahasiswa? - Christ Billy Aryanto; Silvester Bambang Aditama (Universitas Andalas, 2019)
Some people have a habit to listen to music while reading book. The genre and the tempo of the music that people listened to while reading the book may differ. This research is done specifically to understand whether slow tempo classical music may affect undergraduate students’ reading comprehension. This study is experimental research with randomized two-groups design, post-test only. The participants in this research consist of 78 undergraduate students that were divided into two groups, which are experimental group (38 participants) and control group (40 participants) with the age ranged 18-24 years old. The participants were divided into two groups using the randomization technique. The classical music used in this research was called Clair de Lune by Claude Debussy and used TKD-1R to measure reading comprehension. The result of this research showed that classical music, especially with the slow tempo, did not have a significant effect on reading comprehension. The result of this study supported previous research which argued that classical music, specifically slow tempo music, did not interfere with the participants. Therefore, reading activity while listening to music can be done simultaneously. Keywords: classical music, reading comprehension, undergraduate students, slow tempo